2020
DOI: 10.1016/j.annonc.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, multicenter, two cohort study of 160 mg osimertinib in EGFR T790M-positive non-small-cell lung cancer patients with brain metastases or leptomeningeal disease who progressed on prior EGFR TKI therapy

Abstract: Background: Up to 40% of patients with non-small-cell lung cancer (NSCLC) and epidermal growth factor receptor (EGFR) mutations treated with EGFR tyrosine kinase inhibitors (TKIs) present with disease progression in the central nervous system (CNS), either as brain metastases (BM) or leptomeningeal metastases (LM). Osimertinib (80 mg), a third-generation, irreversible, oral EGFR TKI, has shown efficacy in active CNS metastases. However, efficacy of osimertinib 160 mg in BM or LM is unclear. Patients and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 23 publications
3
80
0
Order By: Relevance
“…A major advance in the management of these tumors has been the development of brain-penetrant tyrosine-kinase inhibitors. 9,10 These agents not only prevent or delay intracranial treatment failure, but are also increasingly utilized as primary therapy for patients with brain metastases instead of localized interventions such as radiotherapy, an intervention potentially associated with longterm quality of life impairment. 11 Selpercatinib (LOXO-292), a highly potent and selective RET inhibitor, has marked and durable efficacy in patients with treatment-naïve or platinum chemotherapy-treated RET fusion-positive NSCLCs.…”
Section: Introductionmentioning
confidence: 99%
“…A major advance in the management of these tumors has been the development of brain-penetrant tyrosine-kinase inhibitors. 9,10 These agents not only prevent or delay intracranial treatment failure, but are also increasingly utilized as primary therapy for patients with brain metastases instead of localized interventions such as radiotherapy, an intervention potentially associated with longterm quality of life impairment. 11 Selpercatinib (LOXO-292), a highly potent and selective RET inhibitor, has marked and durable efficacy in patients with treatment-naïve or platinum chemotherapy-treated RET fusion-positive NSCLCs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Ahn et al [106] , retrospectively analyzing 22 patients with LM from EGFR T790M mutated NSCLC treated with osimertinib 80 mg/day: ORR was 55% (95%CI: 32-76), and median OS was 18.8 months (95%CI: 6.3-NC). Park et al [107] also reported an intracranial ORR of 55.0%, median PFS of 7.6 months (95%CI: 5.0-16.6),…”
Section: Role Of Egfr Tyrosine Kinase Inhibitors In Lm From Nsclcmentioning
confidence: 93%
“…Osimertinib 80 mg daily ORR 55% Median OS 18.8 months Park et al [107] , 2020 Ahn et al [109] , 2016 Prospective 29 (4 with LM) AZD3759 3/4 patients (75%) had a significant reduction of EGFR expression 1/4 patients (25%) had a CSF conversion in two consecutive samples…”
Section: Retrospective 22mentioning
confidence: 99%
“…In the past two decades, signi cant advances have been made in the treatment of NSCLC that have improved our understanding of the biology and pathogenesis of tumor disease. The use of small molecule tyrosine kinase inhibitors and immunotherapy can increase the survival bene t in lung cancer patients, but drug resistance is a problem in some patients after treatment [3,4]. Currently, the overall cure and survival rates of NSCLC remain low.…”
Section: Introductionmentioning
confidence: 99%